2017 IEEE International Geoscience and Remote Sensing Symposium (IGARSS) 2017
DOI: 10.1109/igarss.2017.8127518
|View full text |Cite
|
Sign up to set email alerts
|

Validating SMAP SSS with in situ measurements

Abstract: Highlights  Sea surface salinity retrieved from SMAP radiometer is validated with in situ data  SMAP achieved 0.2 PSU accuracy on a monthly basis in tropics comparing with Argo OI  SMAP can track large salinity changes occurred within a month consistent with buoy  SMAP SSS retrieved in Mediterranean sea and BOB assessed with ship TSG and Argo STS Highlights (for review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 9 publications
3
34
0
Order By: Relevance
“…The buoy data remained over satellite and Argo measurements during March to August 2016, which may be most likely caused by a failure of the mooring salinity sensors. It indicates that satellite SSS can be used as real‐time QC of buoy 1‐m salinity, consistent with the previous result of Tang et al (). By comparing satellite SSS, the Argo data from BOA_Argo data set and buoys, we examined the time series of all TAO buoys and found that there are six suspicious buoys with large drifts in their time series that are inconsistent with SMAP, SMOS, and Argo data (Figures c and d).…”
Section: Comparison With Tropical Pacific Tao Buoyssupporting
confidence: 92%
See 1 more Smart Citation
“…The buoy data remained over satellite and Argo measurements during March to August 2016, which may be most likely caused by a failure of the mooring salinity sensors. It indicates that satellite SSS can be used as real‐time QC of buoy 1‐m salinity, consistent with the previous result of Tang et al (). By comparing satellite SSS, the Argo data from BOA_Argo data set and buoys, we examined the time series of all TAO buoys and found that there are six suspicious buoys with large drifts in their time series that are inconsistent with SMAP, SMOS, and Argo data (Figures c and d).…”
Section: Comparison With Tropical Pacific Tao Buoyssupporting
confidence: 92%
“…Previous studies conducted salinity data quality assessments by comparing satellite SSS with in situ measurements, but mainly for SMOS and Aquarius satellite data products (Garcia‐Eidell et al, ; Kao, Lagerloef, Lee, Melnichenko, Meissner, et al, ; Köhler et al, ; Lee, ; Maqueda et al, ; Reagan et al, ; SMOS‐BEC Team, ; Tang et al, ). Due to the late launch of the SMAP satellite, there are few related studies (Meissner et al, ; W. Tang et al, ). To the best of our knowledge, there is not yet long time series quality comparison analysis of gridded salinity products released by the main data centers of three satellites.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent ability to document SSS from satellites, providing global coverage in less than 8 days at ~50‐ to 150‐km resolution, allows us to enrich our knowledge of SSS mesoscale variability. Notable in this regard are the key contributions of the SSS data sets issued from the Soil Moisture and Ocean Salinity (SMOS; 2010 and ongoing), Aquarius (2011–2015), and Soil Moisture Active Passive (2015 and ongoing) satellite missions (Kerr et al, ; Lagerloef et al, ; Reul et al, ; Tang et al, ). Based on these satellite data sets, the signature of mesoscale variability and eddies on SSS has been documented in various regions, in particular, in the North Atlantic subtropical gyre, in the Gulf Stream region, in the Gulf of Mexico, in the Bay of Bengal, in the southern Indian Ocean, and in line with the occurrence of tropical instability waves in the Atlantic and Pacific Oceans (Fournier et al, , ; Kolodziejczyk et al, ; Lee et al, , ; Melnichenko et al, ; Reul et al, ; Yin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The newest V3.0 release of SMOS has bridged the accuracy gap between it and SMAP by increasing near‐land RFI parameterization and thus signal‐to‐noise ratio, although interference still remains an issue (Boutin et al, ). RFI parameterization has also increased with the most recent V4.2 release of SMAP‐CAP, which provided for more realistic SSS field particularly where Aquarius could not (Tang et al, ). This suggests that SMAP‐CAP and SMOS are more effective at capturing primary MJO signals than Aquarius‐CAP, although discrepancies may be attributable to near‐land noise parameterization, temporal sampling, and the number of primary events over the lifetime of the product.…”
Section: Resultsmentioning
confidence: 99%